Studi Toponimi Identitas Keanekaragaman Hayati di Kapanewon Imogiri - Yuyun Prohatining Rahmah; Rizqi Budi Arum; Fahada Hartika (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2026)
Toponymy is an onomastics that studies place names. The act of naming places can be interpreted as a human endeavor to recognize identity and understand everything around them. The name of a place is not merely a physical object, but rather carries symbolic meaning as a form of human self-actualization and their relationship with nature. This place naming is not just a marker of identity, but also represents a deep connection between humans and nature. The objective of this research is to understand toponymy as an identity of biodiversity and local wisdom in the Kapanewon Imogiri region. The data used consists of place names, such as ‘padukuhan’ (hamlets) and ‘Kalurahan’ (villages) in Kapanewon Imogiri, as well as a literature study conducted by gathering relevant literature reviews, books, and journals on toponymy and biodiversity. This research method comprises data and information collection, data analysis, and data presentation. The study employs a documentation method with a descriptive approach. The application of Toponymy as an identity of biodiversity and local wisdom in the Kapanewon Imogiri area reveals that 20 padukuhan names in Kapanewon Imogiri are toponyms referring to local tree names, namely Kedungjati, Nogosari, Pelemantung, Putat, Kalidadap I, Kalidadap II, Mandingan, Salaman, Miri, Jati, Jatirejo, Pelemadu, Pucunggrowong, Mojolegi, Bendo, Pundung, Cengkehan, Nogosari I, Nogosari II, and Karangasem. These place names connected to local flora are expected to encourage efforts for biodiversity conservation.